THE AYLI DAĞ OPHIOLITE SEQUENCE (CENTRAL-NORTHERN TURKEY): A FRAGMENT OF MIDDLE JURASSIC OCEANIC LITHOSPHERE WITHIN THE INTRA-PONTIDE SUTURE ZONE - Göncüoglu, M.Cemal; Marroni, Michele; Sayit, Kaan; Tekin, U.Kagan; Ottria, Giuseppe; Pandolfi, Luca; Elero, Alessandro (Ofioliti, 2012)
The Ayli Dağ ophiolites occur as an independent tectonic unit within the Intra-Pontide suture zone, central-northern Turkey. They crop out, together withthe other units of the Intra-Pontide suture zone, at the top of the Late Cretaceous-Middle Paleocene foredeep sediments of the Sakarya Terrane. The Ayli Dağophiolites sequence include in its lower part a mantle sequence consisting of not less than 2-3 km-thick peridotites, topped by 500-600 m-thick layered gabbroswith alternating, dm- to m-thick layers of spinel-bearing dunites, melatroctolites, troctolites, ol-gabbros and leucogabbros. The gabbro sequence is overlainby a sheeted dyke complex, that shows a transition to 100-200 m-thick massive basaltic lava flows followed by 600-800 m-thick massive and pillow lavasand breccias alternating with ophiolite-bearing arenites and cherts.Geochemical evaluation of the mafic lavas and dykes reveals three distinct chemical groups that reflect melt generation within an intra-oceanic subductionsystem. Among these, the first group shows island-arc tholeiite (IAT)-like features, showing very-depleted characteristics (very high Zr/Nb, low Zr/Y and Nb/Y)ratios coupled with light rare-earth (LREE)-depleted chondrite-normalized patterns. The second group is more akin to back-arc basin basalts (BABB); it displaysnormal mid-ocean ridge basalt (N-MORB)-like high-field strength element (HFSE) distribution except for depletion in Nb, and flat REE patterns. The third groupis somewhat similar to the second one, displaying BABB-like characteristics, but it is more enriched in terms of absolute trace element abundances.The radiolarian cherts sampled from the top of the pillow lavas yielded less-diverse but characteristic radiolarian assemblages indicating the middleBathonian to early Callovian ages.The Ayli Dağ Ophiolite is the first finding of back-arc type oceanic lithosphere in the Intra-Pontide suture zone. Together with previous data obtainedfrom basalts in the mélange from the Intra-Pontide suture zone, this finding represents a proof that an intra-oceanic subduction within the Intra-Pontide oceanicbasin occurred in the Middle Jurassic time.